2011
DOI: 10.1121/1.3598430
|View full text |Cite
|
Sign up to set email alerts
|

Full scale model investigation on the acoustical protection of a balcony-like façade device (L)

Abstract: The acoustical insertion losses produced by a balcony-like structure in front of a window are examined experimentally. The results suggest that the balcony ceiling is the most appropriate location for the installation of artificial sound absorption for the purpose of improving the broadband insertion loss, while the side walls are found to be the second best. Results also indicate that the acoustic modes of the balcony opening and the balcony cavity resonance in a direction normal to the window could have a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…The maximum insertion loss was 7 dB. Tong et al [48] also indicated the importance of acoustic modes in shaping the insertion loss spectra.…”
Section: Balconiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The maximum insertion loss was 7 dB. Tong et al [48] also indicated the importance of acoustic modes in shaping the insertion loss spectra.…”
Section: Balconiesmentioning
confidence: 94%
“…A full scale experimental study on the insertion loss of a balcony-like structure in the presence of sound absorption, has been completed by Tong et al [48], inside a dual-chamber laboratory facility built for the ISO140-3 test. High density 1-inch thick fibreglass was used as the sound absorption.…”
Section: Balconiesmentioning
confidence: 99%
“…El-Dien and Woloszyn 5 investigated the effects that inclined parapets and ceilings have on a balcony's insertion loss. May, 2 Hothersall et al, 6 Lee et al, 7 and Tong et al 8 showed that balconies can provide acoustical protection if they are installed with acoustic treatments. Kropp and B erillon 9,10 used modal approach to study the low-and mid-frequency noise inside balcony cavities with rigid and non-rigid boundaries.…”
Section: Introductionmentioning
confidence: 97%
“…In urban streets, balconies are likely to be subjected to road traffic noise levels that may interfere with speech communication. Earlier research into environmental noise on residential balconies has mainly focused on road traffic noise and has also involved a range of methods from full scale measurements 1-5 to scale modeling [6][7][8][9][10][11][12][13] and theoretical models. [4][5][6][7][9][10][11][14][15][16] A concise review of most of this literature has been developed.…”
Section: Introductionmentioning
confidence: 99%